PENGALAMAN PENGGUNAAN LAYANAN KONSELING ONLINE PADA GENERASI Z - Noferdy, Rahmat; Tanaya, I Wayan Nathan Fanza; Putri, Putu Adinda Mahadewi Restu; Lestari, Made Diah (Psikologi UHAMKA, 2023)
Currently, most people are starting to realize the importance of mental health, including Generation Z. This makes counseling services increasingly needed to deal with complaints related to mental health. Technological developments have facilitated the emergence of platforms that provide online counseling services so that they can be accessed by everyone, especially Generation Z. This study aims to find out the experience of using online counseling services for Generation Z so that later they can be used as evaluation material in improving and developing online counseling services. This research is qualitative research using the constructive realism method in the form of an open-ended survey that is distributed online. The survey was made to find out what platforms or websites were used by respondents, what was the respondent's experience in using online counseling, respondents' reasons for choosing online counseling, what were respondents' expectations of online counseling services, services that had met respondents' expectations, the quality of the platform used, the quality of psychologists in providing online counseling services, perceived advantages, and disadvantages of online counseling, as well as ways to improve the quality of online counseling services according to respondents. Thematic analysis was carried out on data from 33 respondents who had accessed online counseling. The majority of respondents expect that online counseling will provide a solution to their problems. Based on the research conducted, 51.5% of respondents considered that there was good quality in terms of the platform they used and 42.4% of respondents considered that there was good quality in terms of the psychological services they received. In addition, as many as 54.5% of respondents also had good experiences when accessing online counseling services from the platforms they used. Online counseling services were chosen because they are considered cheaper, have more secure privacy, have more flexible timing, can be accessed anywhere, and minimizes the negative stigma they receive when consulting about perceived complaints. On the other hand, online counseling has several limitations, such as the duration of counseling which tends to be short, psychologists who are felt to be less professional, and limitations on platform features that need to be improved.